Cognitive abilities - a new direction in burnout research. Issue 5 (3rd September 2021) - Kulikowski, Konrad
ABSTRACT: The prominent burnout models overlook cognitive abilities, that is quite surprising when we consider a) the emerging body of evidence suggesting that burnout is negatively associated with cognitive functioning and b) the tremendous positive role of cognitive abilities in the world of work. Thus, in this conceptual paper, drawing inspiration from the cognitive abilities scholarship and the Job Demands-Resources theory (JD-R), we attempt to put forward a model of the role of the general cognitive ability in burnout formation. We challenge the view that burnout merely impairs cognitive functioning. We propose that the cognitive ability decreases burnout by fostering job resources and buffering cognitive job demands but also that the cognitive ability might generate specific types of job demands. Our theoretical elaboration might help to clarify the emerging burnout – cognitive functioning research, offering insights into how and why the cognitive ability, as a type of personal resources within the JD-R framework, might affect burnout. The proposed conceptual model might spark critique and provoke further debate over the role of cognitive abilities in burnout, inspiring new cognitive directions in burnout research.